The parents’ experience in taking care of their children with cerebral palsy - Simões, Cibele Cristina (2013)
ABSTRACT The care demands of individuals with cerebral palsy may pose physical and emotional burdens on their relatives. Therefore, nurses should intervene so as to meet the needs of the family as well as of the patient. The objective of this study was to understand the experience of parents who take care of their child with cerebral palsy. This qualitative case study was performed at a health center in Botucatu, São Paulo, Brazil. Data were collected, after receiving the approval of the Ethics Committee, and then organized according to Bardin’s content analysis. The analysis of the statements allowed for grouping the results into five thematic categories: leisure activities, prejudice, care-related difficulties, the fulfillment from taking care of your children; and the lack of professional support. The discourses permitted to identify the essential aspects involved in caring for the relatives, who may also fall ill due to the difficulties comprising this experience. Descriptors: Cerebral Palsy; Child Care; Nursing.